Hubungan Status Gizi, Tingkat Konsumsi Fe dan Tingkat Stres dengan Siklus Menstruasi Remaja - Dina Salsabila; Yasir Farhat; Nurhamidi Nurhamidi (Jurusan Gizi Poltekkes Kemenkes Banjarmasin, 2021)
Background: Women who have reached the age of puberty will experience menstruation that appears every month. One of the disorders of menstruation is menstrual cycle disorders. According to Riskesdas in 2010, it showed that irregular menstrual cycles in women aged 10-59 years in Indonesia reached 13.7%. Objectives: To determine the relationship of nutritional status, Fe consumption rate and stress level with menstrual cycle of adolecents at SMA Negeri 2 Banjarbaru. Methods: Nutritional status data were obtained through direct measurements, while data on Fe consumption rate, stress levels and menstrual cycles were obtained through questionnaires on Google Form. This type of research is analytic observational with a cross sectional approach. Data analysis using Chi Square correlation test Î±= 0.05. Results: Most of the experience normal menstrual cycle (65,4%), with good nutritional status (79,5%), rarely consume foods high in Fe (67,9%) and with stress level moderate (33%). Results of the relationship test showed that there was a relationship between nutritional status, Fe consumption rate and stress level with menstrual cycle of adolescents in SMA Negeri 2 Banjarbaru. Conclusions: Most of the experience normal menstrual cycle, with good nutritional status, rarely consume foods high in Fe, with stress level moderate. There was a relationship between nutritional status, Fe consumption level and stress level with menstrual cycle of adolescents in SMA Negeri 2 Banjarbaru.